Theorizing the Addressive Audience in Children's Digital Video Production. (January 2020) - Pandya, Jessica Zacher; Low, David E.
In this article, we examine how children ages 8 to 10 characterized the audiences of digital videos they made in school. Children's perceptions of their viewers reflected, and in many cases complicated, current theorizing about the vast potential audiences of digital texts. Our analysis of videos and interview data surfaces several findings pertaining to how children characterized their audiences. Children discussed their desire to inform viewers, their deliberate choices about language use vis-à-vis their viewers, ways they predicted and steered audience emotions, and the affective dimensions of sharing one's video with different audiences. These findings suggest that educators and researchers ought to foreground issues of addressivity when theorizing the question of audience for children's digital products. They also raise questions concerning authentic audience in an age of increasing concern about children's safety and security in online worlds.